2021
DOI: 10.1097/j.jcrs.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Surface light scattering from 1-piece hydrophobic acrylic intraocular lenses with hydroxyethyl methacrylate: contralateral observation for 7 years

Abstract: Quantitative and intraindividual comparison of surface light scattering up to 7 years postoperatively confirmed the suppression with Clareon IOLs: the slight increase suggested no risk up to 12 years after implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Experimental and clinical studies demonstrated that the new hydrophobic acrylic IOL with HEMA is free from glistenings and surface light scattering. [2][3][4][5][6][7] Large-scale clinical evaluation of this IOL, however, has not been reported.…”
mentioning
confidence: 99%
“…Experimental and clinical studies demonstrated that the new hydrophobic acrylic IOL with HEMA is free from glistenings and surface light scattering. [2][3][4][5][6][7] Large-scale clinical evaluation of this IOL, however, has not been reported.…”
mentioning
confidence: 99%
“…The difference in contrast sensitivity between the two groups was most noticeable (Table 2 ). This result was the most meaningful, and it was more prominent than the existing monofocal IOL study [ 9 ]. Although the measuring instrument was different in the previous study, the AULCSF was not statistically significant in either group for up to 7 years after surgery.…”
Section: Discussionmentioning
confidence: 61%
“…However, the average value was better in the CN group, and further research over a longer period of time is required. In the previous study, surface light scattering was less in IOLs with HEMA, and this difference increased as the follow-up period did [ 9 ]. As time passes, it is thought that similar results can be obtained with multifocal IOLs; this study was not expected to show a significant difference, due to our limited follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations